Modelling the economic impact of the tripartite free trade area: Its implications for the economic geography of Southern, Eastern and Northern Africa - Andrew Mold; Rodgers Mukwaya (Journal of African Trade, 2016)
This study evaluates the economic impact of the proposed COMESA-SADC-EAC Tripartite Free Trade Area (TFTA) on 26 African countries. It uses the Global Trade Analysis Project (GTAP) computable general equilibrium (CGE) model and database to measure the static effects of the establishment of the TFTA on industrial production, trade flows and consumption in the TFTA. The results indicate a significant increase in intra-regional exports as a result of tariff elimination, boosting intra-regional trade by 29%. Particularly encouraging is the fact that the sectors benefiting most are manufacturing ones, such as light and heavy manufacturing, and processed food. Concerns have been raised that industrial production in the TFTA could concentrate in the countries with highest productivity levels - namely, Egypt and South Africa. Simulation results suggest that these fears are exaggerated, with little evidence of concentration of industries in the larger countries.
Keywords: F13; F15; 330; Tripartite free trade area; General equilibrium; Free trade area; Economic integration